Placement of ultra-high performance concrete for inclined-surface pavement. Issue 7 (3rd July 2022) - Shin, Tae Yong; Kim, Jae Hong; Koh, Kyung-Taek; Ryu, Gum-Sung; Wang, Kejin
Abstract : Ultra-high performance concrete (UHPC) shows high strength, high ductility under tensile loading, and high durability. Self-compacting ability is one of the most important merit of UHPC, but high fluidity paradoxically limits concrete pavement application for slope casting. This paper investigates the behaviour of fresh UHPC at rest and proposes a rheological criterion for UHPC to be cast on an inclined slab. Computational fluid dynamics analysis is adopted and, consequently, a criterion ensuring zero-flow state of UHPC is determined together with the boundary effect of formwork. An in-situ criterion in terms of the slump flow is also proposed by applying the empirical formula relating the slump flow to the yield stress. Mock-up slope casting verifies the proposed criterion with three UHPC mixes showing slump flow of 500–700 mm. The results of this study could be used as a basic criterion for application of UHPC to inclined-surface pavement.